Multi Controllers Architecture with Adaptive Monitoring in SDWMN In-Band - Silva, Bruno Ramos e; Araujo, Madson R.; Ferreira, Ibirisol F.; Figueiredo, Gustavo B. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2017: Anais do XXXV Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos, 2017)
Software Defined Wireless Mesh Networks (SDWMN) enable more intelligent and programmable wireless networks. SDWMN with in-band control plane can optimize resource utilization when compared to out-of-band network architectures, because in-band can exempt the need of additional physical or virtual interfaces and legacy protocols to coordinate the control plane traffic. This traffic can also be engineered by SDN and make use of its possible benefits. However, there are many challenges to be dealt with SDWMN in-band, such as network auto-configuration during start-up, scalability and control plane overhead over the data plane. To overcome these limitations, we propose in this paper a multi controllers architecture with adaptive monitoring in SDWMN in-band which objective is to reduce control plane overhead and delay while improving network scalability. The work is implemented as a proof-of-concept in the OpenWiMesh framework. Results show it effectively reduce switch-controller latency and control plane overhead, as well as enabling higher scalability. We also show our monitoring solution enables better wireless network view and uses at least near half the bandwidth compared to a SNMP solution.